2012
DOI: 10.1039/c2dt31065a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of β-O-4 lignin model dimers by a ruthenium-xantphos catalyst

Abstract: Hydrogenolysis reactions of so-called lignin model dimers using a Ru-xantphos catalyst are presented (xantphos = 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene). For example, of some nine models studied, the alcohol, 2-(2-methoxyphenoxy)-1-phenylethanol (1), with 5 mol% Ru(H)(2)(CO)(PPh(3))(xantphos) (18) in toluene-d(8) at 135 °C for 20 h under N(2), gives in ~95% yield the C-O cleavage hydrogenolysis products, acetophenone (14) and guaiacol (17), and a small amount (<5%) of the ketone, 2-(2-methoxyphenoxy)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 54 publications
(89 reference statements)
3
99
0
1
Order By: Relevance
“…However, attempts to cleave models more similar to the actual lignin structural motifs afforded cleavage products only in low yield. [356] Instead, ad ouble dehydrogenated substrate was found to have chelated to the ruthenium metal centre, inhibiting further catalytic activity.A na cetylated keto-bether model on the other hand did undergo cleavage,yielding both the acetophenone and propiophenone,b ut also al arge amount of condensation products.P reliminary small-scale experiments on an acetylated Kraft lignin did seem to suggest cleavage of the lignin, but the products could not be unambiguously identified. [357] Ruthenium-triphos complexes have also proved competent catalysts for the cleavage of 2-aryloxy-1-arylethanols.…”
Section: Methodsmentioning
confidence: 99%
“…However, attempts to cleave models more similar to the actual lignin structural motifs afforded cleavage products only in low yield. [356] Instead, ad ouble dehydrogenated substrate was found to have chelated to the ruthenium metal centre, inhibiting further catalytic activity.A na cetylated keto-bether model on the other hand did undergo cleavage,yielding both the acetophenone and propiophenone,b ut also al arge amount of condensation products.P reliminary small-scale experiments on an acetylated Kraft lignin did seem to suggest cleavage of the lignin, but the products could not be unambiguously identified. [357] Ruthenium-triphos complexes have also proved competent catalysts for the cleavage of 2-aryloxy-1-arylethanols.…”
Section: Methodsmentioning
confidence: 99%
“…30 Zhang et al have shown that woody lignin is catalytically hydrogenated to guaiacol and syringols at 235 C under 6 MPa H 2 , and has obtained 46% (based on lignin) phenolic compounds. 31 Other catalysts, such as CuCr oxide, 32 Co-Mo-S/Al 2 O 3 , 33 activated carbon-, alumina-or silica-supported Ru [34][35][36][37] or Pt, 38,39 have also been reported in hydrogenation of lignin or model compounds to monomeric phenols. Nickel-based catalysts have shown excellent chemoselectivity for aromatic products or high activity for C-O bond cleavage, as reported by Hartwig 40 and Rinaldi.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of metal complexes have been shown to effectively cleave ␤-O-4 model lignin compounds [12][13][14][15][16]. For the production of monomeric phenols, vanadium(V) complexes with O/N donor ligands are amongst the most promising homogeneous catalysts, Fig.…”
Section: Fig 2 Degradation Of ␤-O-4 Model Lignin Compounds By Vanadmentioning
confidence: 99%